Oligo(ethylene imine)‐grafted glycidyl methacrylate linear and star homopolymers: Odd–even correlated transfection efficiency. Issue 10 (6th April 2021) - Pafiti, Kyriaki S.; Kepola, Eleni J.; Vlasiou, Manolis C.; Yamasaki, Edna N.; Patrickios, Costas S.; Mastroyiannopoulos, Nikolaos P.; Phylactou, Leonidas A.; Théato, Patrick
Abstract: The present study aims to investigate an odd–even effect of the number of ethylene imine units in the side‐groups of totally abiotic synthetic polymers on their efficiency in DNA transfection. A library of fifteen polymers was fabricated. Two star homopolymers and one linear homopolymer based on glycidyl methacrylate were synthesized and used as precursors to which five linear oligo(ethylene imine)s (OEI) were grafted. The number of ethylene imine groups of the OEIs was varied. Specifically, ethylene diamine, diethylene triamine, triethylene tetramine, tetraethylene pentamine, and pentaethylene hexamine were used. Each of these fifteen OEI‐grafted polymers was evaluated in terms of their efficiency to transfer plasmid DNA encoding firefly luciferase in C2C12 mouse myoblast cells. The transfection efficiency displayed an odd‐even pattern, with all OEI‐grafted polymers with an odd number of ethylene imine repeating units exhibiting higher transfection efficiency compared with those possessing an even number of ethylene imine repeating units. The odd–even effect was more pronounced for the star polymers with longer arms (degree of polymerization, DP = 100), while in case of the linear polymers, the odd–even effect was only observed for the lowest polymer loading. The cytotoxicity of the OEI‐grafted polymers also followed an odd–even pattern, with the OEI‐grafted star polymers with an arm DP of 100 and the linear polymers clearly presenting an odd‐even effect, while the cytotoxicity of the OEI‐grafted star polymers with an arm DP of 20 slightly increased with the number of ethylene imine repeating units. Abstract :